Pheromone Signaling Methods and Protocols - Touhara, Kazushige.; Touhara, Kazushige. (Methods in Molecular Biology,, 2013)
Providing experimental methods and protocols for performing pheromone research in a variety of organisms ranging from invertebrates to vertebrates, Pheromone Signaling: Methods and Protocols covers a wide spectrum of experimental approaches necessary for handling pheromone molecules, measuring receptor response and neural activation, and analyzing behavioral output. A great deal of progress has been made in understanding the molecular mechanisms underlying pheromone action, largely due to the discovery of receptor genes, the advancement of imaging techniques, and key multi-disciplinary approaches including aspects of organic chemistry, biochemistry, molecular biology, electrophysiology, and behavioral science. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips for troubleshooting and avoiding known pitfalls.   Authoritative and practical, Pheromone Signaling: Methods and Protocols details the key methodologies utilized in laboratories all over the world, making them accessible to those who want to begin investigation in the area of pheromone research.